2018
DOI: 10.1039/c8ra07680d
|View full text |Cite
|
Sign up to set email alerts
|

Interface conjugation enhances the interface adhesion performance of carbon fiber-reinforced phthalonitrile composites by π–π stacking

Abstract: Cross-linking products and graphene can interact with each other through π–π stacking and promote the formation of interface conjugation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The peeling of carbon fibers and resin matrix may be one of the reasons for the unsatisfactory flexural strength of the composites. According to previous reports, 14 under the condition of no interfacial modification, the interfacial strength of AN resins CFRP depends on the conjugation effect between the cured product and the surface of carbon fiber. the curing products of DCI resins are triazine 16 and lack a large conjugated structure such as phthalocyanine, which may be the reason for the weaker interfacial strength of DCI resins.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The peeling of carbon fibers and resin matrix may be one of the reasons for the unsatisfactory flexural strength of the composites. According to previous reports, 14 under the condition of no interfacial modification, the interfacial strength of AN resins CFRP depends on the conjugation effect between the cured product and the surface of carbon fiber. the curing products of DCI resins are triazine 16 and lack a large conjugated structure such as phthalocyanine, which may be the reason for the weaker interfacial strength of DCI resins.…”
Section: Resultsmentioning
confidence: 86%
“…[9][10][11][12][13] For the AN resins, the rich-aromatic mainchain and curing product (such as isoindoline, phthalocyanine and triazine) can guarantee excellent thermostability. It also can form a π-π conjugation with the surface of carbon fiber to enhance the bonding strength of resin-fiber interface, 14 and make the resin and fiber compatible. Recently, our laboratory has introduced dicyanoimidazole (DCI) into the resin field, 15,16 and designed a brand new AN resin-DCI resins.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Subsequently, researchers found that different catalysts, including amines, phenols, carboxylic acids, and inorganic salts, could drastically reduce the curing temperature and reduce the curing time. [7][8][9] This promoted the development of PN resin, 9,11 which has happened rapidly over the past 20 years. [12][13][14][15][16][17][18] Among these PN catalysts, the catalysts containing -NH 2 have the highest outstanding catalytic performance and have been widely used, [19][20][21][22][23][24] such as p-BAPS, 25 m-APB, 26 4-APN, 5 etc.…”
Section: Introductionmentioning
confidence: 99%